Prevalensi dan determinan pencabutan gigi permanen di Poliklinik Gigi dan Mulut Puskesmas Klungkung I tahun 2015 - Komang Hendra Supradnyana; Louise Cinthia Hutomo; Ni Wayan Septarini (Bali Dental Journal, 2019)
Introduction: Tooth extraction is a routine action performed by a dentist for years. The cause of tooth extraction is different for each region and is influenced by the local culture. In general, the causes of tooth extraction are dental caries, periodontal diseases, fracture, impacted teeth or malposition, orthodontic care, persistence, prosthesis condition, dental supernumerary and preparation of patients who will undergo radiotherapy. This study was conducted to determine prevalence and determinant of primary tooth extraction in Poliklinik Gigi dan Mulut Puskesmas Klungkung I. Method: This study is a descriptive study with cross sectional approach in Dental Clinic Primary Health Care Klungkung I. This study used secondary data from detailed dental care report on 2015, in a total of 114 teeth extracted with 103 teeth of them included the inclusion criteria. Result: The results are based on age, with the age group 46-55 years is the highest. By sex, women are more than men (50.5%). Based on residence, the subjects in rural area are more frequent than in the urban area with 68%. The most common causes of permanent tooth extraction are periodontal disease with 55 teeth of 103 teeth (53.4%) followed by caries 23 teeth (22.3%), retained dental roots 22 teeth (21.4%), and periapical abscess 3 teeth (2.9%). Conclusion: The main reason of primary tooth extraction is periodontal disease.